Optic nerve head change in non-arteritic anterior ischemic optic neuropathy and its influence on visual outcome - Jonas, Jost B.; Papastathopoulos, Konstantinos I.; Rensch, Florian (PLOS ONE, 2012)
Purpose To evaluate changes in cup/disc (C/D) diameter ratios and parapapillary atrophy in patients with non-arteritic anterior ischemic optic neuropathy (NA-AION), using morphometric methods. Methods The clinical non-interventional study included 157 patients with unilateral or bilateral NA-AION. Optic disc photographs taken from both eyes at the end of follow-up were morphometrically examined. Results Follow-up was 86.3±70.3 months. Horizontal and vertical disc diameters (P = 0.30;P = 0.61, respectively), horizontal and vertical C/D ratios (P = 0.47;P = 0.19,resp.), and size of alpha zone and beta zone of parapapillary atrophy (P = 0.27;P = 0.32,resp.) did not differ significantly between affected eyes and contralateral normal eyes in patients with unilateral NA-AION. Similarly, horizontal and vertical disc diameters, horizontal and vertical C/D ratios, and size of alpha zone and beta zone did not vary significantly (all P>0.05) between the unaffected eyes of patients with unilateral NA-AION and the eyes of patients with bilateral NA-AION. Optic disc diameters, C/D ratios, size of alpha zone or beta zone of parapapillary atrophy were not significantly associated with final visual outcome in the eyes affected with NA-AION (all P>0.20) nor with the difference in final visual acuity between affected eyes and unaffected eyes in patients with unilateral NA-AION (all P>0.25). Conclusions NA-AION did not affect C/D ratios nor alpha zone and beta zone of parapapillary atrophy. Optic disc size was not related to the final visual acuity outcome in NA-AION.